Ultraxtor - Low Resources High Yield Benchtop Agarwood Essential Oil Extractor - Mohd Haslizam, Abdullah; Mohd Hafizu, Zakaria; Muhamad Sollehudin, Ibrahim; Ahmad Damanhuri, Mohamad Yussof; S. A., Che Ghani (2016)
Endangered wild species of agarwood have been substituted with cultivated agarwood and are suitable to grow in Malaysian climate. More than 100 local agarwood farmers face challenge to extract the high value agarwood essential oil. The extraction facilities are normally using foreign technologies such Thais and Vietnamese which are not optimized to process local agarwood species. The extraction process with conventional hydrodistillation process requires continuous personnel monitoring and highly dependent on operator’s experience. The objective of this innovation is to introduce new benchtop automatic temperature controlled agarwood oil extraction plant for use by local farmers. This benchtop agarwood essential oil extractor named μltraxtor manipulates the temperature distribution in the system by optimizing the boiler heat source and condenser efficiency in a compact benchtop platform to control the rate of extracted agarwood oil in order to achieve high extraction yield and high essential oil quality. The high ratio of extracted oil to the dry wood enables local farmers to produce their own oil at their farms or premises economically.